The correlation between the depth extent of Tuohy epidural needle with body mass index (BMI) to achieve loss of resistance in patients undergoing epidural anesthesia - Hartawan, I Gusti Agung Gede Utara; Senapathi, Tjokorda Gde Agung; Aribawa, I Gusti Ngurah Mahaalit; Parami, Pontisomaya; Pradhana, Adinda Putra; Syamsuddin, Johanis Bosco Troy (DiscoverSys Inc., 2019)
ABSTRACTBackground: Anesthesia management in obesity is quite challenging. Epidural anesthesia become one of the choices. The attention should be addressed in order to prevent the misidentification of epidural space. The estimation of the depth extent of epidural space becomes crucial, especially in obese patients due to an accumulation of subcutaneous and epidural adipose tissue, which consequently complicate the epidural catheter insertion. This study aimed to analyze the correlation of the depth extent of Tuohy epidural needle to achieve loss of resistance between normal-weighted and obese patients.Method: This study was conducted with 56 adult patients aged 17 to 65 years who underwent elective surgery by epidural anesthesia inserted at level L2-L3 or L3-L4 interspace. Subjects are divided into normal and obese groups. Shapiro-Wilk and chi-square tests were used in the normality test. For normally distributed data, an independent t-test was used to test the hypothesis, otherwise, we used Mann-Whitney test Results: The results showed that the loss of resistance in epidural needle insertion procedures was 60 mm in a patient with BMI more than 30 kg/m2 and 50 mm in those with BMI <30 kg/m2 (p<0.001).Conclusion: The loss of resistance depth in epidural Tuohy needle insertion is significantly determined by BMI.